Direct memberships in foreign copyright collecting societies as an entrepreneurial opportunity for music publishers – needs, challenges, opportunities and solutions - Stephan Klingner; Mihail Miller; Michael Becker; Frank Schumacher (Journal of Cultural Economics, 2021)
In the competitive, increasingly international music business, publishers are developing new ways to increase effectiveness and efficiency of the monetization of the copyrights they own or manage. Driven by various needs, publishers become entrepreneurs in new markets by choosing the path of direct memberships in foreign copyright collecting societies, rather than entrusting sub-publishers or taking the detour through their domestic copyright collecting society. Since with great power comes great responsibility, publishers as entrepreneurs are pursuing various economic opportunities, but at the same time are also facing great challenges. This paper aims at studying the motivation, obstacles and potentials and deriving possible solutions for this step and thus improving the understanding of as well as supporting publishers in this entrepreneurial activity.
Keywords: 330; Music publishers; Sub-publisher; Copyright collecting societies; Copyright management; Exploitation of music copyrights; Royalties